Econometric Analysis of Macroeconomic to Age-Specific Mortality Rate in Malaysia: Evidence from Panel Data - Robiaatul Adawiah Edrus; Zailan Siri; Mohd Azmi Haron; Muhammad Aslam Mohd Safari; Mohammed K. A. Kaabar (Journal of Mathematics)
Human mortality is unanticipated and unavoidable, particularly in light of the recent COVID-19 pandemic. Insurance companies, actuaries, financial institutions, demographers, and the government may suffer catastrophic losses as a result of imprecise mortality estimates. Understanding the factors that contribute to mortality at the population level can help the government improve its efforts to promote health and reduce health inequalities. Consequently, the present study utilizes an econometrics model to estimate Malaysia’s mortality rate, with macroeconomic factors as explanatory variables. The present study employed the unemployment rate, pension liabilities, gross domestic product, education expenditure, and healthcare expenditure as explanatory variables. The empirical results imply that the fixed effects model is feasible when using panel data across specific age groups. Moreover, the fixed effects model is devoid of cross-sectional dependency, heteroscedasticity, and serial correlation. The findings reveal that the unemployment rate, gross domestic product, and education expenditure all have a significant influence on the mortality rate. However, pension liabilities and health expenditure have an insignificant relationship with the mortality rate. The fixed effects model is demonstrated to be a robust model that fits the Malaysian scenario with an R-squared of approximately 84.69%. The present study is novel due to the fact that the model established between explanatory variables and the mortality rate shows a significant relationship, which can be helpful in forecasting the mortality at population level as a preparation for the post-COVID-19 mortality. The present study aims to contribute to the development of an effective support mechanism by rectifying Malaysia’s socioeconomic inequalities in order to mitigate the COVID-19 increase in mortality rate. Therefore, the Malaysian government is strongly encouraged to examine its expenditure on education and gross domestic product in order to improve the mortality rate, particularly among the adult and older population.